Answer:
$67.20
Step-by-step explanation:
84 x .05
4.2
84 x .25
21
84-21
63
63 + 4.2
67.20
Answer:
m = 2, n = - 3
Step-by-step explanation:
Given the 2 equations
2m + 3n = - 5 → (1)
5m + 3n = 1 → (2)
Subtract (2) from (1) term by term to eliminate n
2m - 5m = - 5 - 1
- 3m = - 6 ( divide both sides by - 3 )
m = 2
Substitute m = 2 into either of the 2 equations and solve for n
Substituting into (1)
2(2) + 3n = - 5
4 + 3n = - 5 ( subtract 4 from both sides )
3n = - 9 ( divide both sides by 3 )
n = - 3
Answer:
First option is the correct choice.
Step-by-step explanation:
y - Q = 3(x - P)
3P - Q = 3x - y
Best Regards!
The answer is 5/8 because they both are divisable by 10
Answer:
(-1,-2) OR x = -1 and y = -2
Step-by-step explanation:
y = 3x + 1
y = -x -3
so you would first multiply everything on y = -x -3 by 3 and get 3y = -3x -9
so then you would add 3y = -3x -9 to y = 3x + 1 (<u> to eliminate the x</u> )which would be 4y = -8 then divide by 4 and get <u><em>y = -2</em></u>
then you plug in y = -2 into any one of the equations but to make it easier i am going to plug it into y = -x -3 so now it would be -2 = -x - 3 then, add 2 to both sides which would be 0 = -x -1 then add 1 to both side 1 = -x then multiply both sides by -1 and get <u><em>x = -1</em></u>
<u><em>SO your answer would be </em></u> (-1,-2) OR x = -1 and y = -2 ( both of them are correct but it depends on what the teacher taught you)